Endoscopic retrograde cholangiopancreatography versus endoscopic ultrasound for tissue diagnosis of malignant biliary stricture: Systematic review and meta-analysis - De Moura, Diogo; Moura, Eduardo; Bernardo, Wanderlei; De Moura, Eduardo; Baraca, Felipe; Kondo, André; Matuguma, Sérgio; Almeida Artifon, Everson (Endoscopic Ultrasound, 2018)
Background and Aims: There are no systematic reviews comparing the use of endoscopic retrograde cholangiopancreatography (ERCP)-based brush cytology and forceps biopsy and endoscopic ultrasound (EUS)-guided fine-needle aspiration (FNA) for the diagnosis of malignant biliary stricture; so in this revision, we will compare ERCP against EUS-FNA for tissue diagnosis of malignant biliary stricture. Design: A systematic review was conducted of comparative studies (prospective or retrospective) analyzing EUS and ERCP for tissue diagnosis of malignant biliary stricture. Materials and Methods: The databases Medline, EMBASE, Cochrane, LILACS, CINAHL, and Scopus were searched for studies dated previous to November 2014. We identified three prospective studies comparing EUS-FNA and ERCP for the diagnosis of malignant biliary stricture and five prospective studies comparing EUS-FNA with the same diagnosis of the other three studies. All patients were subjected to the same gold standard method. We calculated study variables (sensitivity, specificity, prevalence, positive and negative predictive values, and accuracy) and performed a meta-analysis using the Review Manager (RevMan) 5.3 software. Results: A total of 294 patients were included in the analysis. The pretest probability for malignant biliary stricture was 76.66%. The mean sensitivities of ERCP and EUS-FNA for tissue diagnosis of malignant biliary stricture were 49% and 75%, respectively; the specificities were 96.33% and 100%, respectively. The posttest probabilities positive predictive value (98.33% and 100%, respectively) and negative predictive value (34% and 47%, respectively) were determined. The accuracies were 60.66% and 79%, respectively. Conclusion: We found that EUS-FNA was superior to ERCP with brush cytology and forceps biopsy for diagnosing malignant biliary strictures. However, a negative EUS-FNA or ERCP test may not exclude malignant biliary stricture because both have low negative posttest probabilities.